Association between dietary potassium intake and severe headache or migraine in US adults: a population-based analysis - Xu, Lisi; Zhang, Cong; Liu, Yan; Shang, Xiuli; Huang, Daifa (Frontiers in Nutrition, 2023)
Background: Migraine is a prevalent neurovascular headache disorder. The link between dietary potassium and blood pressure has been established. We sought to delineate the relationship between dietary potassium intake and the prevalence of migraines. Methods: We conducted a cross-sectional analysis using data from the National Health and Nutrition Examination Survey (NHANES) spanning 1999-2004, comprising 10,254 participants aged ≥ 20 years. Participants who reported severe headaches or migraine in the self-report questionnaire were identified as migraineurs. A 24-hour dietary recall methodology was used to assess dietary potassium intake. Multivariate regression analysis and restricted cubic spline (RCS) modeling were utilized to elucidate the relationship between dietary potassium and migraines. Results: Among the 10,254 participants, 20.1% were identified with migraine or severe headaches. The adjusted odds ratio (OR) for migraine occurrence in the Q2 dietary potassium intake (1771-2476 mg/d) was 0.84 (95% CI: 0.73-0.97, p = 0.021) compared to the lowest quartile (Q1, ≤ 1771 mg/d). The relationship between dietary potassium and migraine exhibited an L-shaped pattern (non-linear, p = 0.016) with an inflection at approximately 1439.3 mg/d. In the subgroup analysis, when compared to Q1, who had the lowest dietary potassium intake, the adjusted OR for Q2 in females, those in the medium-high household income group, and with a Body Mass Index (BMI) ≥ 25 kg/m 2 were as follows: (OR, 0.82; 95% CI, 0.69-0.98), (OR, 0.79; 95% CI, 4 0.66-0.95), and (OR, 0.78; 95% CI, 0.66-0.93), respectively. No significant interaction was observed across groups after adjusting for all possible covariates. Conclusion: The relationship between dietary potassium intake and migraine prevalence among US adults appears to follow an L-shaped curve.